2021
DOI: 10.1007/s00335-021-09880-6
|View full text |Cite
|
Sign up to set email alerts
|

SNPs at 3′UTR of APOL1 and miR-6741-3p target sites associated with kidney diseases more susceptible to SARS-COV-2 infection: in silco and in vitro studies

Abstract: Acute Kidney Injury (AKI) is a common manifestation of COVID-19 and several cases have been reported in the setting of the high-risk APOL1 genotype (common genetic variants). This increases the likelihood that African American people with the high-risk genotype APOL1 are at increased risk for kidney disease in the COVID-19 environment. Single-nucleotide polymorphisms (SNPs) are found in various microRNAs (miRNAs) and target genes change the miRNA activity that leads to different diseases. Evidence has shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Previous researches demonstrated that sex could have a significant impact on infection outcomes and was linked to fundamental variations in immune responses to the diseases in human ( Safdar et al, 2021 ; Fischer et al, 2015, Klein and Flanagan, 2016). For example, men have a significantly higher prevalence of hepatitis A (a viral liver disease) and tuberculosis (a bacterial infection) than women (Guerra-Silveira and Abad-Franch, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches demonstrated that sex could have a significant impact on infection outcomes and was linked to fundamental variations in immune responses to the diseases in human ( Safdar et al, 2021 ; Fischer et al, 2015, Klein and Flanagan, 2016). For example, men have a significantly higher prevalence of hepatitis A (a viral liver disease) and tuberculosis (a bacterial infection) than women (Guerra-Silveira and Abad-Franch, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, miRNA expression has also been found to play a crucial role in developing SARS-CoV-2 infection susceptibility in kidney disease. Evidence showed that the efficiency of the interaction between miRNAs and disease-related target genes could be affected by single-nucleotide polymorphisms (SNPs), and people with common genetic variations in the APOL1 gene or high-risk APOL1 genotype were shown to be more likely to develop kidney disease associated with SARS-CoV-2 infection ( Safdar et al, 2021 ). Since miR-6741-3p targets the 3’ UTR region of APOL1 , it may partially inhibit APOL1 expression and, therefore, help to alleviate kidney complications in patients with COVID-19.…”
Section: Studies On Comorbiditiesmentioning
confidence: 99%
“…Since miR-6741-3p targets the 3’ UTR region of APOL1 , it may partially inhibit APOL1 expression and, therefore, help to alleviate kidney complications in patients with COVID-19. Additionally, miR-6741-3p targets some APOL1 -related genes that interact directly with kidney disorders, perhaps, leading to SARS-CoV-2 infection ( Safdar et al, 2021 ). Accordingly, miR-6741-3p could represent a valuable therapeutic target for COVID-19-associated kidney diseases whose regulatory role on APOL1 should be further studied in the future.…”
Section: Studies On Comorbiditiesmentioning
confidence: 99%
“…Widiasta, Ahmedz et al, in their review, reports a number of ACE-2 associated gene enhancers and gene silencer miRNAs, of which the miR-29, a fibrotic gene silencer and reported fibrotic-protectant, is proposed for further studies as a potential biomarker [109] . In-silico studies analyzing the role of miRNAs as pathological biomarkers have also demonstrated a potential correlation between differential expression of miR-6741-3p during kidney diseases and their susceptibility to SARS-CoV-2 infection, thereby demanding a further in-depth analysis of miR-6741-3p as a potential target [110] . Srivastava, Swayam Prakash et al, in their paper, suggested that the miRNAs that have been reported to alter the ACE-2 expression level in COVID-induced diabetic kidney diseases, including nephropathy and glomerulosclerosis, could be analyzed for their diagnostic roles and reports a number of miRNAs including, miR-125b, miR-143, miR-145, miR181a, which could be targeted for further studies [111] .…”
Section: Mirnas As Therapeutic Biomarkermentioning
confidence: 99%